Diversity and Distribution of Macrofungi in the Aikmel Area of Mount Rinjani National Park - Sri Anjar Wani; Edi Muhamad Jayadi; Risa Umami (Jurnal Biologi Tropis, 2026)
Indonesia, recognized as a megabiodiversity country, harbors rich biological resources including fungi, which play vital ecological and economic roles. This study aims to analyze the diversity and distribution patterns of macrofungi in the Aikmel Resort area of Mount Rinjani National Park, Lombok. A descriptive–exploratory approach was conducted through field surveys using transect plots in two research stages. Data collection included species identification and measurement of environmental parameters such as temperature, light intensity, soil pH, and humidity. The results of the first stage recorded 40 species, while the second stage identified 37 species. After combining both datasets and removing duplicate species, a total of 68 unique macrofungal species were obtained, belonging to Basidiomycota, Ascomycota, and Mycetozoa. These species were distributed across various orders, families, and genera, with Agaricales and Polyporales as the dominant groups. Most macrofungi were found on decayed wood, indicating its importance as the primary substrate. Diversity analysis revealed a moderate level of diversity with relatively low dominance, fairly even species distribution, and high species richness. Environmental factors such as temperature, soil pH, light intensity, and humidity influenced the variation in macrofungal community structure between the two stages. In conclusion, the Aikmel Resort area exhibits high macrofungal diversity with dynamic community structure influenced by environmental conditions and substrate availability, highlighting its ecological importance as a reservoir of fungal biodiversity.